2009
DOI: 10.1248/bpb.32.1
|View full text |Cite
|
Sign up to set email alerts
|

Current Application and Technology of Functional Multineuron Calcium Imaging

Abstract: Here we describe recent applications and technical advancements of functional multineuron calcium imaging (fMCI), which monitors the firing activity of more than a thousand neurons through their somatic Ca 2؉ signals. fMCI is used for analysis of various neural circuits under normal and pathological conditions. In vitro fMCI is made more sophisticated by using multipoint illumination and scanning technology with spinning-disk and low-laser-intensity imaging, electron-multiplying charge-coupled device cameras, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 185 publications
(223 reference statements)
0
4
0
Order By: Relevance
“…Then, each mouse brain was immersed in this ice-cold solution bubbled with a gas mixture of 95 % O 2 and 5 % CO 2 , and 300 μm-thick coronal slices were prepared using a vibratome (VT1000, Leica). After preparation, the slices were recovered for over 30 min at room temperature in an artificial cerebrospinal fluid (aCSF) consisting of: (in mM) 127 NaCl, 26 NaHCO 3 , 1.5 KCl, 1.24 KH 2 PO 4 , 1.4 MgSO 4 , 2.4 CaCl 2 , and 10 glucose [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, each mouse brain was immersed in this ice-cold solution bubbled with a gas mixture of 95 % O 2 and 5 % CO 2 , and 300 μm-thick coronal slices were prepared using a vibratome (VT1000, Leica). After preparation, the slices were recovered for over 30 min at room temperature in an artificial cerebrospinal fluid (aCSF) consisting of: (in mM) 127 NaCl, 26 NaHCO 3 , 1.5 KCl, 1.24 KH 2 PO 4 , 1.4 MgSO 4 , 2.4 CaCl 2 , and 10 glucose [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…After Fluo-4 AM loading, cortical slices were transferred to a perfusion chamber (RC-22, Harvard Apparatus) attached to a LSM510META confocal laser microscopy system (Carl Zeiss) and perfused with physiological aCSF containing: (in mM) 127 NaCl, 26 NaHCO 3 , 3.3 KCl, 1.24 KH 2 PO 4 , 1.0 MgSO 4 , 1.0 CaCl 2 , and 10 glucose [ 44 , 45 ] bubbled with 95 % O 2 and 5 % CO 2 at 37C°. Time-lapse Fluo-4 and TagRFP images were acquired sequentially using an oil-immersion objective (Plan-Neofluar 40×/1.30NA, Carl Zeiss) and Multi-track mode of data collection software (Zen, Carl Zeiss) at 0.5 fps with 512 × 512 pixels.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been reported that GABA‐mediated excitation in the developing hippocampus contributes to the initiation of ictal epileptiform activity (Dzhala & Staley, ). On the other hand, fMCI is usually performed on juvenile tissue, because of the difficulty of loading adult tissue with Ca 2+ dyes (Namiki & Ikegaya, ); we used postnatal day 6–8 animals to overcome this problem. GABA seemed to at least have an inhibitory effect in this study, because the giant depolarizing potential and epileptiform activity described above were inhibited by the GABA A antagonist bicuculline, whereas synchronous activity in this study was caused by bicuculline.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the scan rate, raster scanning could take longer than wide-field imaging CCD cameras but they have higher SNR. Another alternative is to use a spinning-disk confocal microscope with multiple pinholes [24]. For in vivo experiments, however, using a 2P microscope for Ca 2+ imaging allows for deeper imaging of neuronal populations compared to 1P confocal microscopy (see fig.…”
Section: Light-sensitive Actuators and Reporters Of Neuronal Activity -mentioning
confidence: 99%